Mythological motifs of the East in the works of Silver age poetesses - Zvonareva Л.У.; Звонарёв, О.В. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article encompasses analysis of the oriental motives of the Russian literature Silver Age poetesses creative work. Recently there has been published such an anthology is named “1001 poetesses of the Silver age” by the “Prestige book” in Moscow publishing house. The authors claim that, the book is some interest to scientists specializing in emigrant literature, considering that there are many references in the books and periodicals published in Shanghai, Berlin, Prague or Paris, centers of the Russian emigration of those years. The authors believe the oriental motives and mysticism to have become one of the remarkable topics of poetesses creative work of that period including those who would later become eminent Soviet writers and poets with active creative life.